Manajemen Budaya Sekolah Berbasis Karakter dalam Membentuk Disiplin dan Tanggung jawab Siswa di SMK Sasmita Jaya 2 - Hafsah Maryam; Kahfi Pratama; Mila Rindiani; Anita Fathiyaturrahmah; Lili Nurlaili; Imas Masriah; Rian Sri Rahayu (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2026)
This Community Service Program (PKM) was conducted by Master of Educational Management students from Universitas Pamulang, focusing on assisting vocational high school students in developing discipline and responsibility through character-based school culture management. The program aimed to enhance students’ awareness of discipline and responsibility, both individually and collaboratively, foster positive character within the school environment, implement an effective mentoring model, optimize the role of students as facilitators, and analyze the impact of the program on strengthening positive character among vocational students. The method employed a participatory and educative approach combined with digital self-management-based mentoring, implemented through stages of preparation, execution, monitoring, and evaluation-reflection. The activities included initial assessment, introduction to school culture management, internalization of positive values, and interactive discussions. The program was conducted at SMK Sasmita Jaya 2 Pamulang over three days, including core activities and behavioral monitoring. The findings indicate an improvement in students’ understanding of school culture management and the development of positive character. The digital self-management-based mentoring model proved effective in fostering more structured habits, particularly in strengthening positive character within the school environment. The program also demonstrated that graduate students effectively acted as facilitators, mentors, and agents of change. Therefore, this PKM activity successfully guided students in understanding school culture and preparing them for future challenges.